2020
DOI: 10.1038/s41598-020-65597-7
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of prefrontal cortical neurons during conditioning enhances fear memory formation

Abstract: Animals can remember a situation associated with an aversive event. contextual fear memory is initially encoded and consolidated in the hippocampus and gradually consolidated in multiple brain regions over time, including the medial prefrontal cortex (PFC). However, it is not fully understood how PFC neurons contribute to contextual fear memory formation during learning. In the present study, neuronal activity was increased in PFC neurons utilizing the pharmacogenetic hM3Dq-system in male mice. We show that fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In fact, one hour after training in contextual fear conditioning, the transcription of multiple plasticity-related genes is upregulated in the mPFC, leading to immediate changes in synaptic structure and physiology (Bero et al, 2014). Parallel studies also showed that by enhancing the activity of mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one hour after training in contextual fear conditioning, the transcription of multiple plasticity-related genes is upregulated in the mPFC, leading to immediate changes in synaptic structure and physiology (Bero et al, 2014). Parallel studies also showed that by enhancing the activity of mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 27, 2020. ; https://doi.org/10.1101/2020.08.26.269035 doi: bioRxiv preprint mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 79%
“…Temporal inhibition or permanent lesion of the mPFC significantly reduces the freezing behaviors in the fear-conditioned group in rats ( Frysztak and Neafsey, 1991 , 1994 ; Resstel et al, 2006 ). In contrast, elevating the neural activity of mPFC enhances fear expression and memory formation following the conditioning stimulus (CS) ( Shibano et al, 2020 ). Etkin et al (2011) elaborate on the recruitment of ACC and mPFC, two subdivisions of the PFC in emotion regulation and found that the activation of mPFC was seen in the fear expression, retention, and extinction, suggesting that mPFC conveys both safety and danger information.…”
Section: Distinct Roles Of Three Long-range Afferents In the Mpfc In Regulating Complex Behaviormentioning
confidence: 99%